Audit Delay Determinants and the Moderating Role of Audit Firm Reputation in Indonesia - Dianing Ratna Wijayani (CV Edujavare Publishing, 2026)
Indonesian issuers must submit audited annual reports within 120 days of fiscal year-end, yet lengthy audits, audit delay continue to trigger trading suspensions on the Indonesia Stock Exchange (IDX), and prior studies disagree on what drives this delay and whether auditor reputation moderates it. This study examines how profitability, solvency, firm size, and audit committee financial expertise affect audit delay, and whether public accounting firm (KAP) reputation moderates these relationships, extending prior research by adding the audit committee as a predictor, broadening the sample to all IDX-listed firms, and covering the 2020–2024 period. Using purposive sampling, 934 firm-year observations were analyzed with panel data regression; the Chow and Hausman tests indicated that a fixed-effects model was most appropriate. Profitability had a significant negative effect on audit delay, while solvency, firm size, and audit committee expertise showed no significant effect, and KAP reputation did not moderate any of the four relationships; the model explained 57 percent of the variance in audit delay. These results indicate that timely reporting among Indonesian issuers is driven mainly by profitability rather than firm size, leverage, committee composition, or auditor reputation, suggesting audit tenure, audit opinion, and financial distress as promising variables for future research.